2019
DOI: 10.1177/1055665619882566
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Age at Palatoplasty and Speech and Language Outcomes in Children With Cleft Palate: An Observational Chart Review Study

Abstract: Objective: To determine whether timing of palatoplasty (early, standard, or late) is associated with speech and language outcomes in children with cleft palate. Design: Retrospective case series. Setting: Tertiary care children’s hospital. Participants: Records from 733 children born between 2005 and 2015 and treated at the Cleft Craniofacial Clinic of a tertiary children’s hospital were retrospectively reviewed. Exclusion criteria were cleft repair at an outside hospital, intact secondary palate, absence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 93 publications
0
45
1
1
Order By: Relevance
“…Afirma-se portanto, que bons resultados no desenvolvimento da fala também dependem de um bom resultado cirúrgico (Hosseinbad et al, 2015;Shaffer et al, 2020) e a interlocução da equipe cirúrgica com a fonoaudiologia é fundamental para o sucesso da abordagem integral, necessária ao paciente.…”
Section: Resultsunclassified
“…Afirma-se portanto, que bons resultados no desenvolvimento da fala também dependem de um bom resultado cirúrgico (Hosseinbad et al, 2015;Shaffer et al, 2020) e a interlocução da equipe cirúrgica com a fonoaudiologia é fundamental para o sucesso da abordagem integral, necessária ao paciente.…”
Section: Resultsunclassified
“…Formal evaluation of such practices in plastic surgery and related specialties remains a challenge given the paucity of level I and II evidence (Ariyan et al, 2015;Brignardello-Petersen et al, 2015;Naimi-Akbar et al, 2018;Habib et al, 2019;Delaplain et al, 2020). This task is particularly challenging in the cleft population as outcomes are influenced by multiple factors, including cleft size and type (Bykowski et al, 2015;, surgical timing (Eliason et al, 2020;Shaffer et al, 2020), and patient/caregiver socioeconomic status and access to care (Bennett et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies of CP repair have suggested that surgery prior to 13 months of age was associated with improved speech outcomes. 12,13 Many factors contribute to delays in surgical intervention in patients with CP, including the aforementioned patient factors as well as systems-based factors such as operative scheduling and access to care. Last, the increased speech error rates identified in these patients may be related to uncaptured patient factors (eg, developmental delay) that would have correlated with worse speech outcomes regardless of timing of repair.…”
Section: Discussionmentioning
confidence: 99%